2010
DOI: 10.5142/jgr.2010.34.1.068
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Enzymatic Pretreatment for the Production of Fermented Ginseng using Leaves, Stems and Roots of Ginseng

Abstract: :This study sought to optimize the extraction and enzymatic treatment conditions of Panax ginseng leaves, stems, and roots for the production of fermented ginseng. The optimization enhanced the extraction of total saccharide, a nutrient and growth-activating factor for Lactobacillus bacteria. The hydrolysis of ginseng leaves, stems, and roots was tested with eight enzymes (Pentopan, Promozyme, Celluclast, Ultraflo, Pectinex, Ceremix, Viscozyme, and Tunicase). The enzymatic hydrolysis conditions were statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In addition, the polyphenols and flavonoids in ginseng leaf exhibit very potent antioxidant activities [9]. Recent studies have employed new technologies to maximize the herbal benefits of ginseng, and have focused on the development of new ginseng health products [14]. Powders and extracts from ginseng roots have been used to make cosmetics [15].…”
mentioning
confidence: 99%
“…In addition, the polyphenols and flavonoids in ginseng leaf exhibit very potent antioxidant activities [9]. Recent studies have employed new technologies to maximize the herbal benefits of ginseng, and have focused on the development of new ginseng health products [14]. Powders and extracts from ginseng roots have been used to make cosmetics [15].…”
mentioning
confidence: 99%
“…Despite Ceremix having been reported to be effective for the extraction of total saccharides from ginseng leaves, stems, and roots [13], we concluded that Viscozyme was more suitable in our experiments using RGR as the substrate. These results indicate that the polysaccharide hydrolases degraded the RGR polysaccharides, which in turn increased the solubility of the polysaccharides, in accordance with the results of previous studies using vegetable materials as substrates [18,19].…”
Section: Enzyme Screeningmentioning
confidence: 60%
“…For efficient cultivation of lactic acid bacteria during ginseng fermentation, partial enzymatic degradation of ginseng constituents and subsequent use of the resulting hydrolysates as nutritional sources is preferable to supplementation with additional nutrients. Ceremix, a mixture of commercial polysaccharide hydrolases, was reported to be a suitable enzyme in the extraction of total saccharides from ginseng leaves, stems, and roots for use as a pretreatment for the production of fermented ginseng [13]. From an economical viewpoint, enzymatic treatment of ginseng residue may be preferable to similar treatment of whole ginseng roots for the supplementation of nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…The method of enzyme treatment was already established in the previous report [26]. Ginseng leaves, stems and roots were pulverized with a KT-34 machine (Korea Medi Co., Ltd., Korea), and separated by particle size (0.15 mm).…”
Section: Enzyme Treatementmentioning
confidence: 99%
“…Recently, much interest has been brought to the subject of research on the validity and medicinal effectiveness of ginseng leaves and stems, and on the application of such components [26]. It was found that the saponin content of ginseng leaves was approximately 4 to 5 January, 2011 times higher than that of the roots, and at least 9 times higher than that of the stems [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%